Changes in the fruiting landscape relax restrictions on endozoochorous tree dispersal into deforested lands. Issue 2 (17th September 2014) - Martínez, Daniel; García, Daniel; Ewald, Jörg
Abstract Question Passive forest restoration is based on the natural recovery of degraded habitats. However, tree recruitment is frequently hampered in deforested lands. Tree seed dispersal is scarce and spatially constrained, confining the potential of forest regeneration to a narrow band surrounding forest remnants. Understanding how landscape configuration can favour endozoochorous seed dispersal into deforested lands is thus crucial to recover forest extent and the concomitant ecosystem services. Can distance restrictions on seed dispersal be modified as a result of temporal variability of fruit–frugivore systems? Location Deforested montane pastures surrounding fragments of secondary temperate forest, Cantabrian Range, Spain. Methods For 2 yr, we evaluated the patterns of fruit production, frugivorous bird movement and tree seed dispersal through the landscape. Seed dispersal in deforested sampling stations was related to their distance to forest cover and the amount of forest cover in their surroundings. Results The large‐scale spatial distribution of fruits varied strongly between years, with relatively higher fruit production in isolated trees within pastures in the second year, when birds were more frequently observed perching on isolated trees. In both years, few seeds were dispersed into deforested areas, and those dispersed occurred close to forest cover. Nevertheless, seed arrival at longer distances increased during the second year. When more fruits were produced within the pastures, birds more often overcame their reluctance to leave the forest, and this change in frugivore foraging patterns cascaded into the spatial patterns of seed dispersal. Conclusions By influencing frugivore activity, temporal dynamism in fruiting landscapes can relax the restriction on tree seed dispersal into deforested areas. Landscape biological dynamism should be taken into account in order to manage rewilding in European temperate forests.